Proposta de índice de acessibilidade ao transporte de média ou alta capacidade por meio de ônibus: uma abordagem através dos setores censitários do IBGE - Godoi Vieira, Caio Roger (Universidade Federal de São Carlos, 2025)
Transport is a human right that is sometimes not respected or is simply neglected. However, guaranteeing the right to transport is one of the ways to improve the quality of life of the local population. The aim of this study is to create a methodology for identifying the accessibility of a given municipality's neighbourhoods, via bus, to the high-capacity transport hub, using easily accessible tools and quantitative data. To do this, the IBGE census sectors are used as a reference via the Geographic Information System (GIS) to identify which neighbourhoods have the best transport indicators, such as the quality of the route between the home and the bus stop - known as the first mile - and the supply of each bus stop, consisting of a simpler quantitative way of obtaining results without the need for opinion polls. The TOD (Transit Oriented Development) principle and the AHP (Analytic Hierarchy Process) methodology were used as aids. In this way, extensive qualitative surveys of users' opinions were not necessary, transforming this method into an economical, fast and effective way of measuring accessibility to public transport. A case study based on the proposed methodology was conducted in the city of Barueri-SP and the results proved useful in demonstrating the reality of accessibility in the municipality. Using an index with scores from 0 to 10, it was possible to see which sectors and neighbourhoods have the worst and best accessibility indices. Sectors close to main avenues scored well. However, gated communities were more likely to have low scores, as were peripheral neighbourhoods and other fast-growing areas where urban planning has not kept pace with expansion.
Proposal for an accessibility index for medium and high-capacity bus transport: an approach using IBGE census sectors
Propuesta de un índice de accesibilidad para el transporte en autobús de media y alta capacidad: una perspectiva a partir de los sectores del censo del IBGE
Keywords: Acessibilidade; Transporte público; Planejamento da mobilidade urbana; Sistema de informações geográficas; Setores censitários; Accessibility; Public transit; Urban mobility planning; Geographic information system; Census sectors; Accesibilidad; Planificación de la movilidad urbana; Sistema de información geográfica; Sectores censales; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES::PLANEJAMENTO E ORGANIZACAO DO SISTEMA DE TRANSPORTE